Editor’s Note - Fogg, Thomas (Current Musicology, 2013)
There is a nice scene in Annie Hall where Woody Allen’s character, standup Alvy Singer, meets Carol Kane’s character, stage manager Allison Portchnik. Waiting in the wings at a variety show, Singer remonstrates with Portchnik over the scheduling. “What do you mean, ‘next’?” he asks with amazement. “I’m not going after another comedian . . . because they’re laughing . . . so what are you telling me? They’re gonna laugh at him for a couple of minutes then I’ve gotta go out there and get laughs too? How much can they laugh? They’re laughed out!” I know how he feels. Our previous special issue— Experimental Writing about Music, edited by David Gutkin—is impossible to follow. But only in that sense do I relate to Singer: although Experimental Writing has its laugh–out–loud moments, it is also possibly the most ambitious and unique volume of Current Musicology to date. (If you haven’t already, find it at our website or order a hard copy). For the present issue, general operations resume: the articles collected here continue the journal’s unabating commitment to diverse content, high–quality scholarship, and rigorous peer review.